PENGARUH PERSEPSI KARYAWAN TENTANG PENILAIAN KINERJA DAN KOMPENSASI FINANSIAL TERHADAP KEPUASAN KERJA KARYAWAN PT. SEMEN PADANG - Yunita, Yunita; Kumbara, Vicky Brama; Neldi, Mondra (Jurnal Ekonomi Manajemen Sistem Informasi, 2020)
The purpose of this study is to the description of employee perception about performance appraisal, financial compensation, and job statisfaction, to indentify and analyze the influence employee perceptions about of performance appraisal toward financial compensation, to identify and analyze the influence of employee perceptions about performance appraisal toward job satisfaction, to identify and analyze the influence financial compensation toward job satisfaction, and to identify and analyze the influence of employee perception about performance appraisal toward job satisfaction through financial compensation. The type used in this study is descriptive causative research. The population in this study were all employees of PT. Semen Padang totaling 1551 permanent employees. The sample in this study was 192 questionnaires from 318 questionnaires distributed, and using cluster random sampling. The Data were analyzed with the help of Amos software version 22. The results of this study concluded that employee perceptions of performance appraisals significant effect on financial compensation, employee perceptions of performance appraisal effect significant on job satisfaction, financial compensation significant effect on employee job satisfaction, employee perceptions of performance appraisal significantly influence employee satisfaction through financial compensation.